Effects of different land use patterns on soil properties and N2O emissions on a semi-arid Loess Plateau of Central Gansu - Du, Mengyin; Yuan, Jianyu; Zhuo, Macao; Sadiq, Mahran; Wu, Jiangqi; Xu, Guorong; Liu, Shuainan; Li, Jie; Li, Guang; Yan, Lijuan (Frontiers in Ecology and Evolution, 2023)
Nitrous oxide (N2O) is one of the significant greenhouse gases in the atmosphere. Different land use patterns are the sink or source of N2O, which plays a vigorous role in controlling N2O emissions. Yet, how different land use patterns affect soil N2O emissions in the Loess Plateau of Central Gansu is still not clear. Therefore; in order to fill this gap, six different land use patterns, including Picea asperata (PA), Hippophae rhamnoides (HR), Medicago sativa (MS), No-tillage wheat field (NT) and Conventional tillage wheat field (T) were studied. The objective of this study was to examine the impact of different land use patterns on soil properties and N2O emission flux. Our results showed that compared with other treatments, Picea asperata woodland increased the soil bulk density, organic matter and soil water content, total nitrogen accumulation and microbial biomass nitrogen whilst reduced the soil pH. The wheat field is more favorable to accumulating soil nitrate nitrogen and ammonium nitrogen. Moreover, soil N2O emission rates followed the trend of T>NT>HR>GL>MS>PA. In addition, soil physicochemical properties were closely related to N2O emission flux and soil temperature was the most significant factor affecting N2O emission. General, Picea asperata woodland could significantly increased soil nutrient and reduce N2O emissions. We suggest that more forest land should be selected as the optimal site for nitrogen fixation and emission reduction for sustainable development of the terrestrial ecosystem on the Loess Plateau in Central Gansu.